Supramolecular Nanomedicines of In-Situ Self-Assembling Peptides - Zhang, Ying; Yu, Yingying; Gao, Jie (Frontiers in Chemistry, 2022)
Nanomedicines provide distinct clinical advantages over traditional monomolecular therapeutic and diagnostic agents. Supramolecular nanomedicines made from in-situ self-assembling (SA) peptides have emerged as a promising strategy in designing and fabricating nanomedicines. In-situ SA allows the combination of nanomedicines approach with prodrug approach, which exhibited both advantages of these strategies while addressed the problems of both and thus receiving more and more research attention. In this review, we summarized recently designed supramolecular nanomedicines of in-situ SA peptides in the manner of applications and design principles, and the interaction between the materials and biological environments was also discussed.